The Cognitive Science of Imagination and Religion - van Mulukom, Valerie (Journal for the Cognitive Science of Religion, 2020)
Religion and imagination both deal with what is beyond theempirical here and now. In this article, I will argue that imaginationas a capacity is highly important for the development, maintenance,and evolution of religion and the variety of componentsthat together make a religion: (Religious) belief, religious cognitionbroadly, religious events such as miracles, religious agentssuch as deities, religious rituals and experiences, religious textsand narratives, and finally religious art and creativity. I will arguethat the cognitive science of imagination can crucially shed lighton various aspects of religion that previously may have seemedunrelated, and that in fact, perceiving, remembering, and imaginingmay not be as distinct processes from each other as wemight have thought, and indicate what consequences these suggestionsmay have for beliefs as we understand them.